A study on the simulation of psychological and behavioral dynamics in the unsafe state of coal mine workers - Yin, Jueli; Liu, Zhen; Yu, Kai; Kong, Biao; Mou, Xiaowei; Zhang, Xiaolong; Ma, Wanli (Frontiers in Earth Science, 2023)
The coal mine production safety hazards are large and the situation is severe, and coal mine workers are affected psychologically, producing unsafe psychological states and triggering unsafe behavior. It is of great theoretical and practical significance for coal mine safety management to study the interaction of unsafe psychological states of coal mine workers and the dynamic generation mechanism of the emergence process of unsafe behaviors. This paper firstly studies the interactive influence process of unsafe psychological state of coal mine workers and reveals the emergence process of unsafe psychology and behavior of coal mine workers. According to the characteristics of qualitative simulation of safety behavior, safety psychology and unsafe state of coal mine personnel, 23 simulation schemes are designed, and simulation analysis is carried out using QSIM simulation software platform. According to the simulation results of 23 schemes, the dynamic emergence process of safety behavior, safety psychology and unsafe state of coal mine workers was sorted out from the aspects of different states and the intensity of different management measures, and the law of the effect of coal mine workers' safety psychology on safety behavior and safety state was obtained , revealing the interactive influence of coal mine workers' psychology on the unsafe state and the internal evolution mechanism of the emergent process.